INDIGENOUS KNOWLEDGE: ITS ROLE IN THE HEALTH CARE PRACTICES OF THE ANAMALAI HILLS OF COIMBATORE DISTRICT, TAMIL NADU, INDIA - Rajendran, A. (Medknow Publications & Media Pvt Ltd, 1999)
The communication deals wit 9 plant species used as a traditional medicine and the application of indigenous beliefs, knowledge is concerned with their health care practices by the anamalai ills aborigines.